1998
DOI: 10.1002/(sici)1521-4141(199801)28:01<370::aid-immu370>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

β2 -Microglobulin-deficient NK cells show increased sensitivity to MHC class I-mediated inhibition, but self tolerance does not depend upon target cell expression of H-2Kb and Db heavy chains

Abstract: Mice lacking g 2-microglobulin (g 2 m − mice) express greatly reduced levels of MHC class I molecules, and cells from g 2 m − mice are therefore highly sensitive to NK cells. However, NK cells from g 2 m − mice fail to kill g 2 m − normal cells, showing that they are self tolerant. In a first attempt to understand better the basis of this tolerance, we have analyzed more extensively the target cell specificity of g 2 m − NK cells. In a comparison between several MHC class I-deficient and positive target cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 38 publications
2
25
0
1
Order By: Relevance
“…These pellets were dissociated, and the resulting Nonidet P-40 supernatants were subjected to secondary immunoprecipitation, as described above. Nonidet P-40-stable pellets are shown in lanes 1-10; immunoprecipitations from Nonidet P-40 supernatants are shown in lanes [11][12][13][14][15][16][17][18][19][20]. As seen previously in Fig.…”
Section: K B Molecules Whose Export Is Blocked By MCMV Infection Are mentioning
confidence: 83%
See 1 more Smart Citation
“…These pellets were dissociated, and the resulting Nonidet P-40 supernatants were subjected to secondary immunoprecipitation, as described above. Nonidet P-40-stable pellets are shown in lanes 1-10; immunoprecipitations from Nonidet P-40 supernatants are shown in lanes [11][12][13][14][15][16][17][18][19][20]. As seen previously in Fig.…”
Section: K B Molecules Whose Export Is Blocked By MCMV Infection Are mentioning
confidence: 83%
“…Precipitates were resuspended in Nonidet P-40 lysis buffer to disrupt Nonidet P-40-unstable complexes, after which they were recentrifuged to precipitate the Nonidet P-40-stable complexes shown in lanes 1-10. Supernatant remaining from these immunoprecipitations was divided in half and subjected to sequential precipitation with two different Abs, as shown (lanes [11][12][13][14][15][16][17][18][19][20]. All samples in B and C were digested with Endo H. report, Fig.…”
Section: M4/gp34 Does Not Associate Significantly With ␤ 2 M In the Amentioning
confidence: 99%
“…15 Thus, our current data on TAP2 Ϫ/Ϫ NK cells are clearly reminiscent of previous data obtained in ␤2-microglobulin-deficient or TAP-1 knockout mice. 37,38 These studies showed that ␤2-m Ϫ NK cells, while sparing autologous concanavalin A blasts and bone marrow cells, could lyse allogeneic major histocompatibility complex class I Ϫ tumors. In view of our current finding that TAP2 Ϫ/Ϫ NK cells express functional NCR, it is unlikely that they fail to kill PHA blasts because of the lack of still undefined triggering receptor(s).…”
Section: Discussionmentioning
confidence: 99%
“…3D). Importantly, B6 NK cells transferred to a b 2 m À/À environment, rejected MHC class I À leukemia cells equally well, and much better than na€ ve b 2 m À/À mice (35). Similar to NK cells subjected to inhibitory receptor blockade, NK cells could thus still distinguish between MHC class I-sufficient and -deficient malignant cells, despite a reduced rejection of MHC class I À healthy cells.…”
Section: Maintained Tumor Rejection After Nk Cell Transfer To Mhc Clamentioning
confidence: 92%